The Depoliticization of Ecology: Discourse Analysis of Land Conflict in Punclut, North Bandung Region - Kirana Mahdiah Sulaeman; Fadiyah Matni Nurdini; Mustabsyirotul Ummah Mustofa (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
This study discusses the narrative and discourse in the conflict over land use in Punclut, Pagerwangi, North Bandung Region. The local community has managed the water catchment area of the North Bandung area for several decades before coming into conflict with the property company PT DAM which obtained a building permit from the government. Departing from Garet Hardin's Tragedy of the Commons, this research explores the causes of natural degradation in Punclut through a discourse on natural resource control by two warring parties: residents and the government. A qualitative approach with discourse analysis is used to answer research questions using data from interviews, mass media, journal articles, and official documents. The findings of this study are that Hardin's solution to the destruction of natural resources needs to be revised to answer the conditions in Punclut, where there is a local community with sociocultural rules and rationality to manage natural resources with ecological awareness. This community offers an alternative political discourse regarding environmental management: "depoliticization of ecology" and participatory conservation. However, the government and companies' discourse on welfare and economic progress always dominates the discourse in the decision-making process.